The Impact Of Mixed Marriages On The Nationality Of The Couple`S Acquisition And Missing (Comparative Study) - Alkhbor, Sajer; Hariri, Ahmad (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Mixed marriages is a link two different men and women in marital sexual relationship, based on a valid contract in form and substance in accordance with the requirements prescribed in the legislation, differences of nationality between the couple raised several problems lies in the impact of the nationality of both spouses on the other acquisition or missing, were these problems and many others of interest in adopting the doctrine of several positions established by the three principles of jurisprudence, the principle of the unity of nationality in the family, the principle of independence of nationality in the family, and third principle swing between the two principles, avoid disadvantages of both principles achieving the benefit of women, family, and the state, which embraced most of the world currently, had previously oscillating between principles, and through several legislative trends, and international convention as well as the role of large in enshrining the right of women to retain their nationality equal with men. أثر الزواج المختلط على جنسية الزوجين اكتساباً وفقداً ( دراسة مقارنة) الزواج المختلط هو ارتباط شخصين رجل وامرأة مختلفين في الجنسية بعلاقة الزوجية, بناءً على عقد صحيح من الناحية الشكلية والموضوعية وفقاً للشروط المقررة في قانونيهما, فاختلاف الجنسية بين الزوجين أثار عدة إشكالات تكمن في تأثير جنسية كل من الزوجين على الأخر اكتساباً أو فقداً وظهرت في هذا المجال ثلاث مبادئ فقهية, هي مبدأ وحدة الجنسية في العائلة, ومبدأ استقلال الجنسية في العائلة, ومبدأ ثالث متأرجح بين المبدأين, تجنب مساوئ كلا المبدأين محققاً مصلحة المرأة, الأسرة, والدولة, والذي تبنته معظم دول العالم حالياً, بعدما كانت متأرجحة بين المبدأين السابقين, وذلك من خلال عدة اتجاهات تشريعية, وكان للاتفاقيات الدولية دور كبير في تكريس حق المرأة في الاحتفاظ بجنسيتها وتغييرها مساواةً في ذلك مع الرجل.